Study of Biochemical Parameters in Diabetic Patients with and without Diabetic Retinopathy – A Hospital based study - Joshi, I.; Lavaju, P.; Badhu, B.P.; Maskey, R.; Lamsal, M. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetic Retinopathy (DR) is a common, potentially blinding and visually disabling complication of diabetes. Early detection of retinopathy and its progression to severity with routine referral for screening by Ophthalmologist can save vision by timely management. Methods: This was a hospital based cross-sectional study done to study the association of glycated hemoglobin (HbA1c), fasting and postprandial blood sugar, serum lipid profile, serum creatinine and urine albumin in diabetic patient with and without DR. A total of 50 patients with Diabetic retinopathy and 50 patients without diabetic retinopathy were enrolled in this study. All patients included were Type 2 DM aged 35 years and above. Results: The mean HbA1c was 8.62±1.5 and 5.54±1.2, total cholesterol was 228.9±63 and 184.9±39.8 mg/dl, serum triglyceride was 226.6±80.7 and 160.8±45.1 mg/dl, LDL-C was 152.3±49 and 127.2±37 mg/dl and serum creatinine was 1.15±0.45 and 0.66±0.27 mg/dl in diabetic retinopathy group and no diabetic retinopathy group respectively. There was significant association of elevated HbA1c, serum triglyceride, LDL- C and total cholesterol with diabetic retinopathy in patients with type 2 DM. The mean values of serum lipoproteins were higher in the diabetic retinopathy group. Conclusion: Elevated fasting and postprandial blood sugar, glycated hemoglobin, total cholesterol, serum triglyceride, LDL-C, serum creatinine and urine albumin were significantly associated with DR in our study. So, all patients with diabetes mellitus should be screened routinely for serum lipoproteins along with blood sugar profile, as it would help in early detection of diabetic retinopathy.